Speed of stock price adjustment to information arrival in the Middle East and North Africa stock market - Erfanian, Azadeh (2015)
The 2007/08 global financial crisis (GFC) that originated in the financial sector of United States gradually spread to emerging and developing countries via several economic channels with negative spillovers. Stock market activity is one of which was severely affected due to this financial crisis. The Middle East & North Africa (MENA) region, similar to nearly every region of both developing and developed worlds, was not immune from the systemic effect of GFC. Given its importance as a major supplier of energy on the world market, the MENA region is subjected to adverse effect of financial crises. The region also holds many sovereignty funds operating in the markets of industrialized economies, in addition to being an important market for the goods produced in these economies. In this the economic environment, the efficient pricing of financial assets is pertinent and there are few research that have been done on the MENA countries examining how financial assets are priced in these countries. One of the important way to looking at pricing efficiency of assets is the speed of price adjustment. Thus, the major aim of this study was to identify the effect of GFC on the speed of price adjustment, and thus to measure the relative market efficiency of stocks listed in the selected MENA countries. Adopting the speed of price adjustment estimators developed by Theobald and Yallup (2004), this study examines the effects of financial crisis on speed of price adjustment in the MENA countries. The speed of price adjustment was measured during 2005-2012, both including before (2005-2008) and after (2009-2012) the GFC. The speed of price adjustment to both market-wide and firm-specific announcement is also examined in this study. The auto-covariance ratio estimator exhibits decline in the number of days taken to fully adjust new information in some countries and increase in the number of days in others while the ARMA(1,2) showed an increase in the number of days needed to adjust new information between 2005 and 2009. This study also examined that there is no difference in stock performance before and after the announcement day because in efficient market it is impossible for investors to outperform the market at any time. The speeds of price adjustment to both types of firm-specific and market-wide announcements are also determined in this study. Four out of six countries proved under-reaction for 2 to 5 days before GFC and 2 to 6 days after GFC while the other showed an over-reaction just for 2 days before and after GFC. Five out of six country revealed under-reaction that persisted up to 3 days before and after GFC while the other country reported over-reaction for just one day. Observations also were made on two different market- wide announcements. Based on ARMA(1,2) four out of six countries revealed under-reaction that persisted from one to days from the day of new information arrival of national annual budget for both before and after GFC. On the other hand two other countries showed over-reaction for 2 days before and after GFC. Interestingly for national general election announcement three out of six countries showed under-reaction and the other three countries revealed over-reaction between one to three days before and after GFC.